2022
DOI: 10.1002/cne.25305
|View full text |Cite
|
Sign up to set email alerts
|

Exploring links from sensory perception to movement and behavioral motivation in the caudal nidopallium of female songbirds

Abstract: Decision making resides at the interface between sensory perception and movement production. Female songbirds in the context of mate choice are an excellent system to define neural circuits through which sensory perception influences production of courtship behaviors. Previous experiments by our group and others have implicated secondary auditory brain sites, including the caudal nidopallium (NC), in mediating behavioral indicators of mate choice. Here, we used anterograde tracer molecules to define projection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 30 publications
(72 reference statements)
3
10
0
Order By: Relevance
“…Lesions commonly extended along the axis on which the injection was made (Figures 2B-E). Similar to results from previous injections in NC, affected volumes typically extended 250-350 microns in the medial-lateral direction (Bloomston et al, 2022). As in previous reports, song playback resulted in call responses during the song presentation (Dunning et al, 2014(Dunning et al, , 2020.…”
Section: Nc Lesioned Females Were Unchanged In Their Ability To Indic...supporting
confidence: 87%
See 2 more Smart Citations
“…Lesions commonly extended along the axis on which the injection was made (Figures 2B-E). Similar to results from previous injections in NC, affected volumes typically extended 250-350 microns in the medial-lateral direction (Bloomston et al, 2022). As in previous reports, song playback resulted in call responses during the song presentation (Dunning et al, 2014(Dunning et al, , 2020.…”
Section: Nc Lesioned Females Were Unchanged In Their Ability To Indic...supporting
confidence: 87%
“…Previous work has shown that NC is reciprocally interconnected with cells in CM (Vates et al, 1996;Dunning et al, 2018;Bloomston et al, 2022), suggesting that NC and CM may work together to control over courtship behaviors. In support of the idea that modulation of song evaluation and courtship behavior may require the coordination of activity in both of those sites, roughly half of the neurons within NC are GABAergic with projections to CM (Pinaud et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CM projects robustly to other portions of the auditory lobule (NC). CM also receives small amounts of reciprocal input from NC, as evident in some reports that reveal weak projections from NC to CM and others that detected no connection between those areas ( Vates et al, 1996 ; Dunning et al, 2018 ; Bloomston et al, 2022 ). Dunning et al (2018) also found that CM projects into pathways that provide dopaminergic input back to cortical areas (ventral portion of the intermediate arcopallium, AIV).…”
Section: Female Song Preferencementioning
confidence: 81%
“…Here, we turn to consideration of the neural mechanisms that are also shaped by that experience and that underlie the perception and expression of mate preferences. Electrophysiological recordings and pathway tracing studies from many research groups have revealed pathways through which auditory experience is relayed from the ears to the brain (reviewed in Dunning et al, 2018 ; Bloomston et al, 2022 ). Activity originating in hair cells of the inner ear is propagated through a network of auditory neurons in the brainstem and thalamus, and it eventually reaches a forebrain area which is the avian analog of the mammalian primary auditory cortex (Field L) ( Lewicki and Arthur, 1996 ; Grace et al, 2003 ; Amin et al, 2004 ; Meliza and Margoliash, 2012 ; Prather, 2013 ).…”
Section: Female Song Preferencementioning
confidence: 99%